2013
DOI: 10.1111/ced.12138
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the therapeutic efficacy of docetaxel for cutaneous squamous cell carcinoma through the combined inhibition of phosphatidylinositol 3-kinase/AKT signalling and autophagy

Abstract: Early-stage cutaneous squamous cell carcinoma (cSCC) has a favourable prognosis. Metastatic disease is probably associated with chemoresistance mediated through the activation of pro-survival phosphatidylinositol 3-kinase/AKT signalling. Inhibition of activated AKT partially increases chemosensitivity but induces autophagy, the principal lysosomal mechanism for the bulk degradation and recycling of proteins and damaged organelles. The aim of the current study was to test the hypothesis that combined inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Many studies argue that autophagy is implicated in cancer cells resistance to chemotherapy and thus autophagy inhibition could improve the anticancer outcome by resensitizing cancer cells to chemotherapy 17,18,59 . Nevertheless, other reports suggest that autophagy enhances the effect of chemotherapy and radiotherapy inducing cell death 60,61 .…”
Section: Discussionmentioning
confidence: 97%
“…Many studies argue that autophagy is implicated in cancer cells resistance to chemotherapy and thus autophagy inhibition could improve the anticancer outcome by resensitizing cancer cells to chemotherapy 17,18,59 . Nevertheless, other reports suggest that autophagy enhances the effect of chemotherapy and radiotherapy inducing cell death 60,61 .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have reported that increased basal autophagy contributes to resistance to MTIs, although the mechanisms are not clear [34]. Also, it has been reported that increased basal autophagy contributes to resistance to other anticancer drugs, such as the DNAdamaging agent cisplatin, which has a cancer-killing action that depends at least partially on SAC function [22,[35][36][37]].…”
Section: Discussionmentioning
confidence: 99%
“…In this line, an increased expression of the autophagy marker LC3 has been demonstrated in patients with SCC, which was associated with disease progression and prognosis of cancer [ 300 ]. Interestingly, an in vitro study showed that the inhibition of both Akt signaling and autophagy by the lysosomal inhibitor chloroquine enhanced the susceptibility of metastatic SCC cells to docetaxel-induced apoptosis [ 301 ].…”
Section: Inflammation and Skin Cancermentioning
confidence: 99%